Eksistensi dan Peran Dakwah Male Ta Ilayabe di Gorontalo - Perdana, Dian Adi; Sahrain, Elvin; Apriani, Ibnu; Inaku, Rezki; Anuz, Moh. Alwi; Manani, Selitia; Karim, Hapsa (Jurnal Dakwah, 2022)
Male Ta Ilayabe’s character which respected by the local community as ulama. How is the process, strategy, role and legacy of Male Ta Ilayabe's da'wah in Gorontalo. This research is qualitative with descriptive method using observation and interview data collection techniques. The data obtained then it studied, analyzed, interpreted to produce conclusions. The results of this study were his strategy by taking advantage of his position as an assistant of king as well as da’wah to the people of Gorontalo. His populist and simple attitude makes it easy in the process of da’wah. His role of da'wah as a messenger of taxes, the existence of religious-political relations became a factor in the penetration of Islam in the archipelago. His da'wah activities have an impact on changing the social community with the remains of tomb and Hunto mosque which have become religious and cultural tourism destinations in Gorontalo City.